Ubuntuísmo e quilombismo na música de Leci Brandão - Queiroz, Janaína Souza de (2017)
This master’s thesis discuss the participation of the sambist black woman in the context of this afro-brazilian music expression. The text here presented is the result of a reflexion about the following problem: Is there a ubuntu and quilombist perspective in the music compositions of Leci Brandão? The reading, analysis and systematization process of the results started from the following general objective: to analyze ubuntuism and quilombismo in the music compositions of Leci Brandão. The procedures adopted delimited the resources, and because of that, the examined material consists in writing works, music lyrics and interviews of Leci Brandão’s persona, and, as só, the methodology is qualitative, of analytic and deductive character, and the data collect is of the bibliographic and documentary type. The concepts of ubuntu and quilombismo were took as the criterion of analysis for the compositions of Leci Brandão. Another concept also helped in the construction of this work, such as afrocentricity, agency, black feminism and intersectionality to know the contribution of black women in the music context, especially that of samba. Also valuable is the perspective of the interaction of technology and work about the themes approached in this work. The consulted materials, and the content of the analysis were incorporated in the texts, those of which were distributed in four chapters: Introduction; Ubuntu, Quilombismo and Samba; Ubuntuist and Quilombist Ways of Being in Leci Brandão’s Music and Final Considerations.